Penerapan Standar Mutu Pelayanan BPM Di Masjid Agung Sultan Thaf Sinar Basarsyah - Hamzah, Akbar Ali; Arifin, Zainal (Universitas Cokroaminoto Yogyakarta, 2025)
This study examines the management, planning, and implementation strategies of the Sultan Thaf Sinar Basarsyah Grand Mosque Government Agency in improving the quality of service. This study identifies the main problems, namely, the lack of management knowledge among administrators, minimal use of technology, and the lack of effective empowerment of management. This type of research is field research using an interpretive qualitative approach to understand social phenomena from the perspective of participants. The stages in this study include orientation or description, data reduction, and focus selection, followed by in-depth analysis of the data and information obtained. The results of the study indicate that there is a lack of knowledge among mosque administrators, making one cause of the suboptimal improvement in service quality, which should be by utilizing technology there will be an efficient and effective increase in service. Management still needs improvement in time management and communication, as well as empowerment through training stages.